The forgotten rubber: rhinolith formation from a neglected nasal foreign body - Ahmad Shukri, Fatin Aisya; Mohamad, Adam; Johari, Ahmad Hafizuddin (Elsevier Inc., 2026)
Rhinolithiasis is an uncommon condition resulting from progressive mineral deposition around an intranasal nidus, often a neglected foreign body. We report a case of a four-year-old girl who presented with a three-week history of unilateral foul-smelling nasal discharge, fever, and subsequent blood-stained rhinorrhea. She was initially treated as an upper respiratory tract infection, leading to delayed diagnosis. Examination under anesthesia revealed a hard irregular mass within the left nasal cavity. Endoscopic removal demonstrated a rubber foreign body encased in calcified material, confirming rhinolith. The patient received intravenous followed by oral antibiotics with complete clinical resolution on follow-up. This case highlights the importance of maintaining a high index of suspicion for intranasal foreign bodies in children with persistent unilateral fetid discharge. Early nasal endoscopic evaluation is essential to prevent complications and avoid misdiagnosis. Prompt endoscopic removal combined with appropriate antibiotic therapy results in excellent outcomes.